Analisis Layanan Konseling Individual dan Konseling Kelompok - Sufiandi, Adhelia Caroline (Universitas Muria Kudus, 2025)
This research discusses face to face counseling services both individually and in groups as a strategic approach to support individual personal, social and academic development. Individual counseling provides personalized attention to address specific issues, while group counseling leverages social dynamics for shared learning. A comparison of these approaches highlights their respective strengths in enhancing counseling and guidance effectiveness. The analysis reveals that these services complement each other and can be applied according to client needs.